Evidence of Local Extinction and Reintroduction of Aedes aegypti in Exeter, California - Kelly, Erin Taylor; Mack, Lindsey K.; Campos, Melina; Grippin, Crystal; Chen, Tse-Yu; Romero-Weaver, Ana L.; Kosinski, Kyle J.; Brisco, Katherine K.; Collier, Travis C.; Buckner, Eva A.; Campbell, Lindsay P.; Cornel, Anthony J.; et al. (Frontiers in Tropical Diseases, 2021)
Established populations of Aedes aegypti, a mosquito vector of multiple major arthropod-borne viruses, were first found in three California (CA) cities in 2013. From 2013 to April 2021, Ae. aegypti thwarted almost all control efforts to stop its spread and expanded its range to 308 cities, including Exeter, in 22 counties in CA. Population genomic analyses have suggested that multiple genetically distinct Ae. aegypti populations were introduced into CA. However Ae. aegypti collected for the first time in 2014 in Exeter, appeared to be different from three major genetic clusters found elsewhere in CA. Due to intense control efforts by the Delta Vector Control District (DVCD), Ae. aegypti was thought to have been eliminated from Exeter in 2015. Unfortunately, it was recollected in 2018. It was not clear if the reemergence of Ae. aegypti in Exeter was derived from the bottlenecked remnants of the original 2014 Exeter population or from an independent invasion from a different population derived from surrounding areas. The goal of this work was to determine which of these scenarios occurred (recovery after bottleneck or reintroduction after elimination) and if elimination and reintroduction occurred to identify the origin of the invading population using a population genomic approach. Our results support the reintroduction after elimination hypothesis. The source of reintroduction, however, was unexpectedly from the southern CA cluster rather than from other two geographically closer central CA genetic clusters. We also conducted a knockdown resistance mutation profile, which showed Exeter 2014 had the lowest level of resistant alleles compared to the other populations, could have contributed towards DVCD’s ability to locally eliminate Ae. aegypti in 2014.